2023
DOI: 10.5817/cp2023-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Instant messaging and relationship satisfaction across different ages and cultures

Abstract: Research suggests that using IM is generally beneficial for maintaining personal relationships, yet well-being benefits are likely to be conditional on micro- and macro-level variables. This study investigates the link between IM use and relationship satisfaction across age groups using survey data collected from 19 countries (N = 20,358, age range 18–94, Mage = 41.0, SD = 14.6). The multilevel regression results revealed that (1) overall IM use with strong ties is positively related to individuals' satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
0
1
Order By: Relevance
“…Secondly, our findings across both studies speak to the overall generalizability of the reported effects of SNS use on wellbeing across different groups of students. Although previous scholars have suggested that adaptation process may be dependent on the cultural distance between home and host country (e.g., Geeraert et al, 2019), or that the different online platforms that are in use in different societies may have a differential impact (Pang, 2021;Vauclair et al, 2023), our work shows that the psychological processes that underlie the effects are in fact quite similar across different populations, and platforms. The congruence in the observed pattern of relationships among variables is remarkable, especially considering differences in operationalizations between the two studies, and provides a conceptual replication of the results across contexts.…”
Section: Theoretical Implicationscontrasting
confidence: 50%
“…Secondly, our findings across both studies speak to the overall generalizability of the reported effects of SNS use on wellbeing across different groups of students. Although previous scholars have suggested that adaptation process may be dependent on the cultural distance between home and host country (e.g., Geeraert et al, 2019), or that the different online platforms that are in use in different societies may have a differential impact (Pang, 2021;Vauclair et al, 2023), our work shows that the psychological processes that underlie the effects are in fact quite similar across different populations, and platforms. The congruence in the observed pattern of relationships among variables is remarkable, especially considering differences in operationalizations between the two studies, and provides a conceptual replication of the results across contexts.…”
Section: Theoretical Implicationscontrasting
confidence: 50%